This side of paradise - Fitzgerald, F. Scott (Francis Scott), 1896-1940 (Scribner, 2003)
This classic novel, first published in 1920, tells the story of Amory Blaine's moral education and sexual awakening, brilliantly capturing the rhythms of postwar America and the spirit of a generation dedicated to the pursuit of excitement, sophistication, and success.